25 Effect of instructor's real-time feedback using QCPR-classroom device during layperson cardiopulmonary resuscitation (CPR) training on quality of CPR performances: a prospective cluster-randomised trial. (16th April 2018) - Kong, SY; Shin, SD; Song, KJ; Ro, YS; Hong, KJ; Park, JH; Kim, TH; Birkenes, T; Myklebust, H
Abstract : Aim: The evidence supporting delivery of quality cardiopulmonary resuscitation (CPR) is growing and significant attention has been focused on improving CPR education among laypersons perform bystander CPR. The aim of this randomised trial was to assess the effectiveness of instructor's real-time objective feedback during CPR training compared to conventional feedback in terms of trainee's CPR quality. Method: We performed a cluster randomised trial of community CPR training classes at Nowon District Health Community Centre in Seoul. CPR training classes were randomised into either intervention (instructor's objective real-time feedback based on the QCPR Classroom device or control (conventional, instructor's judgement-based feedback) group. Laerdal QCPR Classroom software is a real-time feedback device, which monitors quality of real-time CPR performances of multiple trainees simultaneously. During each training session, trainees practiced CPR five times. The primary outcome was the total CPR score, which is an overall measure of chest compression quality. Secondary outcomes were individual CPR performance parameters, including average number of compressions, average compression depth, percent adequate depth and percent acceptable release. Generalised linear mixed models were used to analyse the outcome data, accounting for both cluster- (random effect) and individual-(fixed effect) level factors. : A total of 149 training sessions (2613 trainees) were randomised into 70 intervention (1262 trainees) and 79 control (1351 trainees) groups. During the training, trainees in the QCPR feedback group significantly increased overall CPR score performance compared with those in the conventional feedback group (model-based mean Δ increment from baseline to session 5: 11.2 (95% CI: 9.2 to 13.2) and 8.0 (6.0–9.9), respectively) with statistically significant between group difference (p=0.02). Individual parameters of compression depth and release also showed higher improvement among trainees in QCPR group with marginal significance (p<0.08 for both). Results: In this randomised trial, QCPR-Classroom based feedback during the CPR training session resulted in improved overall CPR quality. In this randomised trial, QCPR-Classroom based feedback during the CPR training session resulted in improved overall CPR quality. This suggests beneficial effect of instructor's real-time objective feedback on the quality of layperson's CPR performance. Conclusion: The training equipment used in this study (QCPR Classroom) was supported by the Laerdal Medical, but had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data. Conflict of interest: None Funding: None